The Concept of Progressive Business Management according to Goals and Performance as the Basis of Socially Responsible Management - Olga PONISCIAKOVA; Eva Kicova (Communications of International Proceedings, 2021)
The business environment is increasingly characterized by its variability, from dynamic to turbulent. This fact is influenced by the increasing complexity and variability of changes that affect businesses from outside. The complexity of management is therefore indisputable and there are increasing demands on managers to survive and not only to be able to keep their companies on the market but also to develop them. Requirements for improvement are also placed on strategic management, in which it is no longer so crucial to be able to predict developments, but to be able to react in each new variability. Strategic managers must reflect on these changed conditions and adapt their approaches to management to the changing environment, conditions. In practice, this means knowledge and flexible implementation of various support tools or methods to support management and increase efficiency. The paper focuses on one of the mentioned methods - management by objectives (MBO). The aim is based on the analysis of theoretical knowledge to assess and determine the degree of use of MBO in business practice in Slovakia. The intention is based on the assumption that management by objectives is very effective and in companies it may be unknowingly used and it is necessary to know its benefits and make full use of the benefit, which is often neglected and increasing the performance of the company.
Keywords: Management; Goals; Goal Management